2022
DOI: 10.1016/j.jvs.2021.11.071
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of anatomic predictors of abdominal aortic aneurysm remodeling after endovascular repair

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
0
10
1
Order By: Relevance
“…Another negative predictive measure for AAA shrinkage was a larger preoperative infrarenal β angle. A recent systematic review demonstrated that two other studies that investigated AAA remodeling one-year after EVAR did not find significant relations between infrarenal angulation and AAA remodeling—in contrast to this study [ 13 ]. However, both studies were not comparable to this study as one study focused only on the Lombard Aorfix high angulation device and used another definition for neck angle [ 25 ], while the other study demonstrated smaller infrarenal angles with an undescribed measurement method of these angles [ 24 ].…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Another negative predictive measure for AAA shrinkage was a larger preoperative infrarenal β angle. A recent systematic review demonstrated that two other studies that investigated AAA remodeling one-year after EVAR did not find significant relations between infrarenal angulation and AAA remodeling—in contrast to this study [ 13 ]. However, both studies were not comparable to this study as one study focused only on the Lombard Aorfix high angulation device and used another definition for neck angle [ 25 ], while the other study demonstrated smaller infrarenal angles with an undescribed measurement method of these angles [ 24 ].…”
Section: Discussioncontrasting
confidence: 98%
“…The evidence on a relationship between the preoperative AAA diameter and remodeling after EVAR varies greatly between different published studies—as shown in a recent review [ 13 ]. When focusing on studies reporting specifically on AAA remodeling one-year after EVAR, two studies found no correlation, while two others observed that a larger preoperative AAA diameter was related to an increased likelihood of AAA shrinkage [ 22 , 23 , 24 , 25 ]—consistent with the findings of this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These considerations may justify the relatively low incidence of type IA endoleak and graft migration that were observed in the cohort of patients included in this analysis. Indeed, the efficacy of proximal sealing depends on the combination of several patients-related and graft-related factors, such as neck shape, angulations, calcifications, endoprosthesis fixation (barbs, bare metal stents), and the sole occurrence of 2–3 mm PAN growth from the baseline may be insufficient to cause any clinically relevant proximal neck complications [ 29 , 30 , 31 ]. Although this may represent a potential methodological bias, a continuous growth of the PAN has been well documented in most available literature and lifelong follow-up is recommended both in EVAR and FEVAR procedures, especially when hostile anatomical features of the PAN are present [ 32 ], as also suggested by current clinical practice guidelines [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Angulated neck is found to be a predictor for sac enlargement ( 29 ), which is closely linked with postoperative aortic rupture ( 30 ). Sac remodeling, with a close connection with endoleaks, reintervention and mortality, may be affected by hostile neck and AAA volume ( 31 ). There is mounting evidence proving that patients with these hostile anatomical features could suffer from postoperative adverse events more commonly ( 32 35 ).…”
Section: Discussionmentioning
confidence: 99%